Accommodating new vistas. (March 2015) - Gasiorek, Jessica; Giles, Howard; Soliz, Jordan
Abstract: In this Special Issue, we aim to provide a diverse sample of current research that uses and/or extends Communication Accommodation Theory in innovative ways. With this Prologue, we provide a general overview of the tenets and recent developments of theory, discussing how each of the seven original research articles included herein fits in the theory's ever-evolving framework and body of research.